Plan, activity, and intent recognition : theory and pratice / Gita Sukthankar [and others]. - Sukthankar, Gita (Morgan Kaufmann, 2014)
Plan recognition, activity recognition, and intent recognition together combine and unify techniques from user modeling, machine vision, intelligent user interfaces, human/computer interaction, autonomous and multi-agent systems, natural language understanding, and machine learning.
Keywords: Human activity recognition.; Artificial intelligence.; Pattern perception.; Intention.; Artificial intelligence; Human activity recognition; Intention; Pattern perception